Light Scattering Reviews 3 Light Scattering and Reflection - Kokhanovsky, Alexander A. (Environmental Sciences, 2008)
This 3rd volume Light Scattering Reviews is devoted to modern knowledge and milestones in both experimental and theoretical techniques related to light scattering and radiative transport problems. It will consist of 3 parts comprising 11 contributions written by world leading experts in their respective fields. The general focus of the book will be on remote sensing of geophysical media. The first part will be devoted exclusively to studies of single light scattering by particles of different shapes and chemical compositions. The first chapter will review in situ measurements of cloud optical characteristics like cloud extinction and phase function, with the emphasis on ice clouds. Chapter 2 will cover opitcally soft particles common in marine environments and bio-suspensions while Chapter 3 will describe numerical techniques applicable not only to isotropic but also to chiral and anisotropic mdia. The final chapter in this part will deal with spatial symmetries in light scattering problems. This 3rd volume gives a valuable picture of recent developments in the areas of single light scattering, radiative transfer in particulate media and inverse problems of spherical atmospheres. It will further facilitate studies in light scattering media optics and be of importance for researchers across various scientific fields including astronomy, meteorology and geophysics. .